(untitled) (Sebha University Conference Proceedings, 2022)
This study aims at defining administrative and financial corruption. It explains its forms and motives due to its seriousness and its consequences on contemporary societies in terms of the destruction of the political, social and economic structures. It also identifies the international and local efforts (Libya) and their role in combating this phenomenon, and whether the legal mechanisms which Libya applies are sufficient to control this phenomenon. This study also explores whether the bodies entrusted with combating the phenomenon of corruption have the mechanisms that enable them to fully combat this phenomenon. In this study, the researcher relied on the descriptive analytical method. He also relied on scientific research and previous studies related to the subject. The researcher has concluded, that the phenomenon complained of by all countries, that corruption has reached its maximum degree due to the corruption of the state institutions and low levels of social welfare, and the forms of corruption that are multiple and not limited to the public sector only, but even included the private sector. These reasons are due to a complex network of administrative, economic, legal, social and political factors. The international efforts are considered sufficient to reduce this phenomenon if its mechanisms are applied according to the correct methods. The United Nations Convention against Corruption is considered the most comprehensive anti-corruption convention given that it is the result of the concerted efforts of countries and governments and has been ratified by more than 170 countries. The mechanisms that Libya has put in place to eliminate this phenomenon are also capable of combating it if they are applied with all professionalism. It is no secret to anyone that the current situation that Libya is undergoing in terms of political divisions was a catalyst for the spread of the phenomenon of corruption.